Manajemen pembelajaran tahfizh Alquran untuk ketercapaian target hafalan di SMPQ Al-Ihsan - Mutaqin, Daud; Indra, Hasbi; Lisnawati, Santi (Tawazun: Jurnal Pendidikan Islam, 2022)
This study aims to determine the management of Quran memorization learning for target achievement at SMPQ al-Ihsan South Jakarta which includes planning, organizing, implementing, and evaluating learning. This research uses a qualitative approach and descriptive research methods. Data collection techniques include observation, interviews and documentation studies. The results showed that SMPQ al-Ihsan has implemented learning management which includes (1) planning for Quran memorization learning for the achievement of memorization targets: first, determining memorization targets; second, formulating a selection system for prospective musyrifs who will guide students in the Quran halqoh; third, formulating a selection system for students in terms of their ability to memorize the Quran; fourth, determining time allocations; fifth, formulating special programs to help achieve targets. (2) Organizing Quran memorization learning for the achievement of memorization targets is carried out to determine the structure and duties of ustadz/ustadzah and determine tahfizh learning groups consisting of 8 to 10 students. (3) The implementation of effective and conducive Quran memorization learning for the achievement of memorization targets includes classroom management in halqoh Alquran and Quran memorization learning activities. (4) Evaluation of Quran memorization learning for the achievement of memorization targets by looking at student learning outcomes and student abilities according to indicators determined by the school. Abstrak Penelitian ini bertujuan untuk mengetahui manajemen pembelajaran tahfidz Alquran untuk ketercapaian target di SMPQ al-Ihsan Jakarta Selatan yang meliputi perencanaan, pengorganisasian, pelaksanaan, dan evaluasi pembelajaran. Penelitian ini menggunakan pendekatan kualitatif dan metode penelitian deskriptif. Teknik pengumpulan data meliputi teknik observasi, wawancara dan studi dokumentasi. Hasil penelitian menunjukan bahwa SMPQ al-Ihsan telah melaksanakan manajemen pembelajaran yang meliputi (1) perencanaan pembelajaran tahfidz Alquran untuk ketercapaian target hafalan: pertama, menentukan target hafalan; kedua, merumuskan sistem seleksi calon musyrif yang akan membimbing siswa dalam halqoh Alquran; ketiga, merumuskan sistem seleksi peserta didik dari segi kemampuan hafalan Alquran; keempat, menentukan alokasi waktu; kelima, merumuskan program khusus untuk membantu ketercapaian target. (2) Pengorganisasian pembelajaran tahfidz Alquran untuk ketercapaian target hafalan dilaksanakan untuk menentukan struktur dan tugas ustadz/ustadzah serta menentukan kelompok pembelajaran tahfizh yang beranggotakan 8 sampai 10 siswa. (3) Pelaksanaan pembelajaran tahfidz Alquran untuk ketercapaian target hafalan yang efektif dan kondusif meliputi pengelolaan kelas dalam halqoh Alquran dan kegiatan pembelajaran tahfizh Alquran. (4) Evaluasi pembelajaran tahfidz Alquran untuk ketercapaian target hafalan dengan melihat hasil belajar santri serta kemampuan santri sesuai indikator yang telah ditentukan pihak sekolah.